Multi-purpose selectonovation of alternative variants of technological decisions in building - Zavadskas, Edmundas K. (Journal of Civil Engineering and Management, 1996)
The main methodological principles of multi-purpose selectonovation are discussed in the paper. These principles are applied to the development of methods for multi-purpose evaluation of alternative technological desicions in building. A common algorithm and two evaluation criteria are suggested: the relative concession criterion and the criterion of proximity to an ideal point. The values of criteria having been estimated, the rows of alternative variant priorities for the definite years of future period are arranged. Technologinių sprendimų statyboje prognozuojamų variantų daugiatikslė selektonovacija Santrauka. Nagrinėjami pagrindiniai daugiatikslės selektonovacijos metodologiniai principai. Šie principai pritaikomi kuriant prognozuojamų technologinių sprendimų statyboje daugiatikslio įvertinimo metodiką. Pasiūlytas bendras algoritmas ir du variantų vertinimo kriterijai—santykinės nuolaidos ir artumo idealiam taškui. Turint paskaičiuotas kriterijų reikšmes rikiuojamos prognozuojamų variantių prioritetų eilutės atskiriems prognozuojamo periodo metams. Article in Russian. First Published Online: 26 Jul 2012